Unraveling the interactions between neotropical butterflies and ants: the role of chemical communication - Ceballos González, Amalia Victoria (2024)
Interactions between organisms of different species are widely represented across various taxa in nature. Ant-butterfly interactions stand out in Lycaenidae and Riodinidae. Associations between ants and butterflies generally occur, but not exclusively, in the larval stage. Given the chemotaxis of ants, caterpillars have evolved diverse strategies and organs enabling them to explore ant resources and services. Neotropical myrmecophilous butterfly species within Riodinidae have historically received less attention compared to their Lycaenidae counterparts from other regions. This thesis explores life cycles, chemical strategies involving cuticular hydrocarbons (CHCs) as well as the effects of specialized caterpillar organs called Tentacle Nectary Organs (TNOs) and Anterior Tentacle Organs (ATOs) in two riodinid species. The goals of the present work were: 1) Describe and characterize the interactions between two myrmecophilous butterflies and their attendant ants, focusing on aspects such as life cycle, diversity of host plants, attendant ants, and geographical distribution; 2) Identify and compare cuticular hydrocarbons (CHCs) from ants, host plants, and caterpillars; and 3) Identify the effects of ATOs and TNOs on the behavior of attendant ants for one riodinid caterpillar. The natural history data show that the two species studied use many plants as food sources, exhibit contrasting myrmecophily, and can be found in various environments throughout South America. These data may be useful for addressing future ecological, behavioral, or evolutionary issues. The results concerning CHCs indicate that facultative caterpillars exhibit a distinct chemical profile compared to that of plants and ants, with slight influence from the food source and no significant impact from the attending ant species. Additionally, TNOs and, to a lesser extent, ATOs were effective in sustaining ant attention behavior. Here we demonstrate that the close interactions established by caterpillars with ants exert a significant influence on the distribution and selection of host plants, as well as on the behavioral evolution, diversity, and chemical strategies of the caterpillars. Although these results are for caterpillar-ant interactions, they can be extended to other myrmecophilous systems.